Effects of Infant Formula With Human Milk Oligosaccharides on Growth and Morbidity: A Randomized Multicenter Trial. Issue 4 (April 2017) - Puccio, Giuseppe; Alliet, Philippe; Cajozzo, Cinzia; Janssens, Elke; Corsello, Giovanni; Sprenger, Norbert; Wernimont, Susan; Egli, Delphine; Gosoniu, Laura; Steenhout, Philippe
ABSTRACT: Objectives: The aim of the study was to evaluate the effects of infant formula supplemented with 2 human milk oligosaccharides (HMOs) on infant growth, tolerance, and morbidity. Methods: Healthy infants, 0 to 14 days old, were randomized to an intact-protein, cow's milk–based infant formula (control, n = 87) or the same formula with 1.0 g/L 2′fucosyllactose (2′FL) and 0.5 g/L lacto-N-neotetraose (LNnT) (test, n = 88) from enrollment to 6 months; all infants received standard follow-up formula without HMOs from 6 to 12 months. Primary endpoint was weight gain through 4 months. Secondary endpoints included additional anthropometric measures, gastrointestinal tolerance, behavioral patterns, and morbidity through age 12 months. Results: Weight gain was similar in both groups (mean difference [95% confidence interval] test vs control: −0.30 [−1.94, 1.34] g/day; lower bound of 95% confidence interval was above noninferiority margin [−3 g/day]). Digestive symptoms and behavioral patterns were similar between groups; exceptions included softer stool ( P = 0.021) and fewer nighttime wake-ups ( P = 0.036) in the test group at 2 months. Infants receiving test (vs control) had significantly fewer parental reports ( P = 0.004–0.047) of bronchitis through 4 (2.3% vs 12.6%), 6 (6.8% vs 21.8%), and 12 months (10.2% vs 27.6%); lower respiratory tract infection (adverse event cluster) through 12 months (19.3% vs 34.5%); antipyretics use through 4 months (15.9% vs 29.9%); and antibiotics use through 6 (34.1% vs 49.4%) and 12 months (42.0% vs 60.9%). Conclusions: Infant formula with 2′FL and LNnT is safe, well-tolerated, and supports age-appropriate growth. Secondary outcome findings showing associations between consuming HMO-supplemented formula and lower parent-reported morbidity (particularly bronchitis) and medication use (antipyretics and antibiotics) warrant confirmation in future studies. Abstract : Supplemental Digital Content is available in the text